MODEL PENERAPAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD ISLAM TIRTAYASA KOTA SERANG - Hasbi Wahidi (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The aim of this study is to describe the model of the application of character education in Islamic education as well as to study the supporting and inhibiting factors in the application of character education in the learning of Islamic Religious Education at Islamic Elementary School, Tirtayasa in the city of Serang. This study uses qualitative analytical descriptive methods. Data were collected by using in-depth interviews, observation, documentation, and analyzed descriptively qualitatively. The results showed that the model of the application of character education in the teaching of Islamic education in Tirtayasa Islamic Elementary School principals and teachers had made school programs consisting of habits related to religious values, as well as subjects debated by students who would get used to the Dhuha prayer and read the Quran, familiarizing Dhuhur prayer in congregation and Ashar prayer in congregation in the school mosque, and memorizing short letters or juz Amma in Islamic religious education subjects to support student religious relations. In addition students are also required to arrive on time and to be sanctioned if they come late to deliver disciplined students, students are prohibited from cheating during tests to practice honesty of students, and students are required to move class pickets as provided to improve the comfort of answers. The inhibiting factor is that each student has different abilities and different motivations that cause difficulties in conditioning students to learn